Flow Structures and Performance Characteristics of a Savonius Wind Turbine Under Varying Wind Speeds and Blade Angles - Sari, Tria Puspa; Izzah, Anisah Nurul; Satria, Muhammad Hendra Budi; Lamura, M. Danny Pratama; Musyaroh; Shabrina, Dhia Fairuz (JURNAL CRANKSHAFT, 2026)
Savonius wind turbines belong to the class of vertical-axis wind turbines (VAWTs) and are well known for the ability to self-start at low wind speeds without the need for yaw control. Despite these advantages, their aerodynamic efficiency remains lower than that of horizontal-axis wind turbines (HAWTs). In this study, the flow structures and performance characteristics of a Savonius wind turbine are examined using streamline visualization under varying wind speeds ranging from 8 to 10 m/s and blade angles between 100° and 130°. The Reynolds number variations reflect changes in the flow regime and momentum exchange caused by different wind speeds and blade orientations. Across all wind speeds, the 120° blade angle consistently resulted in the most favorable flow conditions. Streamline visualization highlights key flow features, including flow separation, vortex development, and wake structures, which play a critical role in determining aerodynamic efficiency and energy capture. By directly relating Reynolds number variations to observable flow phenomena, this study offers practical insights for aerodynamic optimization. The findings contribute to the development of more efficient Savonius wind turbine designs, particularly for applications in low to moderate wind environments.